Green Leadership and Competence in Green Project Management: Roles of Awareness and Culture - Audiana, Hany; Riyanto, Setyo (Journal of Sustainable Economic and Business, 2026)
Objectives: analyze the effects of green leadership and green competence on green project management, with environmental awareness as a mediating variable and green organizational culture as a moderating variable at PT Cipta Griya Semesta. Methodology: Quantitative, causality design. Population: employees of PT Cipta Griya Semesta; sample: 125 purposively selected respondents (permanent and contract employees directly involved in projects). Analysis used SEM-PLS with SmartPLS 4.0 Finding: Six of eight hypotheses were supported. Green leadership and green competence had positive and significant direct effects on green project management and also significantly affected environmental awareness. Environmental awareness positively influenced green project management and mediated the relationship between green leadership and green project management (H6 accepted). However, environmental awareness did not mediate the effect of green competence on green project management (H7 rejected). Green organizational culture did not moderate the relationship between environmental awareness and green project management (H8 rejected). Conclusion: Green competence appears to improve project outcomes directly without relying on environmental awareness as an intermediary, while green organizational culture functions as an independent predictor rather than a moderator.